2003
DOI: 10.1191/0748233703th185oa
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent transcriptome changes by metal ores on a human acute lymphoblastic leukemia cell line

Abstract: The increased morbidity of childhood leukemia in Fallon, Nevada and Sierra Vista, Arizona has prompted great health concern. The main characteristic that these two towns share is the environmental pollution attributed to metal ore from abandoned mining operations. Consequently, we have investigated the transcriptome effects of metal ores from these endemic areas using a human T-cell acute lymphoblastic leukemia cell line (T-ALL). Metal ore from Fallon significantly increased cell growth after 24, 48 and 72 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This allows for a possible linkage between childhood leukemia and concurrent exposure to both tungsten and cobalt, but research directed more specifically at childhood leukemia is needed to evaluate the role of these metals. In one example, tungsten ore administered to preexisting human leukemia cells in the laboratory increased their growth by 170% compared with control samples over a 72-hr culture period (Sun et al 2003). …”
Section: Discussionmentioning
confidence: 99%
“…This allows for a possible linkage between childhood leukemia and concurrent exposure to both tungsten and cobalt, but research directed more specifically at childhood leukemia is needed to evaluate the role of these metals. In one example, tungsten ore administered to preexisting human leukemia cells in the laboratory increased their growth by 170% compared with control samples over a 72-hr culture period (Sun et al 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Such a connection requires direct biomedical testing. Nonetheless, given that childhood leukemia in Fallon is the "most unique cluster ever reported" (Steinmaus et al 2004) and that Fallon is distinctive environmentally by its elevated airborne tungsten and cobalt particulates, it stands to reason that additional biomedical research is warranted to assess the leukogenicity of airborne tungsten and cobalt (e.g., Fastje et al, 2009;Kalinich et al 2005;Miller et al, 2001;Radcliffe et al, 2010;Steinberg et al 2007;Sun et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Such linkage requires direct biomedical research, which is at least supportable by the cooccurrence of exposure to airborne tungsten and a cluster of childhood leukemia [28, 30]. Tungsten has been evaluated for carcinogenicity, by itself [31, 32] as well as with other metals [3336]. In general, this biomedical research has shown at least the possibility of linkage between exposure to tungsten and cancer.…”
Section: Discussionmentioning
confidence: 99%